2010
DOI: 10.1890/10-0850.1
|View full text |Cite
|
Sign up to set email alerts
|

Community composition and consumer identity determine the effect of resource species diversity on rates of consumption

Abstract: Abstract. The effect of species diversity on ecosystem function is commonly studied within a single trophic level, but less is known about how resource diversity affects species interactions between trophic levels. We conducted a grazing experiment to determine how resource species diversity affects rates of consumption by three species of freshwater zooplankton consumers. We measured the effect of resource diversity on rates of consumption for several resource community compositions. These compositions varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
1
28
1
Order By: Relevance
“…This finding has been previously documented by Narwani & Mazumder [54], who studied the effects of resource species diversity on the clearance rates of cladoceran zooplankton species. In that study, despite consumer-specific effects of changing resource diversity, resource diversity generally reduced consumer consumption rates.…”
Section: Discussionsupporting
confidence: 80%
“…This finding has been previously documented by Narwani & Mazumder [54], who studied the effects of resource species diversity on the clearance rates of cladoceran zooplankton species. In that study, despite consumer-specific effects of changing resource diversity, resource diversity generally reduced consumer consumption rates.…”
Section: Discussionsupporting
confidence: 80%
“…Supporting this idea, the context‐dependence effect of Fox’s Price equation partition (2010) on population variances (which measures the changes in individual species’ variances between high‐ and low‐diversity communities) showed that the dominant species in polycultures 1 and 3 ( S. acutus and P. subcapitata , respectively) were more variable in polyculture than they were in monoculture (see Appendix S2b, Supporting information). Finally, earlier work has shown that in communities with multiple palatable resource species, D. pulex may have an elevated rate of consumption (Narwani & Mazumder 2010). This may have strengthened consumer–resource interactions, destabilizing temporal dynamics (McCann 2000; Rip et al.…”
Section: Discussionmentioning
confidence: 99%
“…2011). Finally, trophic interaction strengths may actually increase with resource species diversity depending on community composition (Narwani & Mazumder 2010), and this can destabilize consumer–resource dynamics (McCann 2000, Rip et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on the combined effect of multiple predators with different resource utilization are unfortunately rare (Jiang and Morin, 2005;Diehl et al, 2013), but most likely better reflect natural communities and enable the direct observation of a major mediator of coexistence: resource partitioning (Chesson, 1991). Narwani and Mazumder (2010) showed that the overall consumption of specialist predators decreases at higher resource diversities, whereas generalist predators show an increase in consumption (Narwani and Mazumder, 2010). Species not directly involved in consumptive interactions are the key to survival of susceptible prey and increased persistence of prey species in more complex food webs (Hammill et al, 2015).…”
Section: Introductionmentioning
confidence: 99%